Legal considerations on environmental policy and the COVID-19 pandemic - Foy Valencia, Pierre Claudio (2020)
This study identifies some premises, by way of context, about the relationship between the environment and COVID-19, and then addresses an aspect of the environmental legal system, that is, environmental policy and relates it to COVID-19. National environment and compares them with examples of transgression of these principles based on the Covid-19.